Peningkatan Motivasi dan Hasil Belajar Bahasa Indonesia Melalui Model Problem Based Learning Kelas V SDN 08/II Rantau Duku - Ullia, Raudatul; Aprizan, Aprizan; Hidayat, Puput Wahyu (Master of Pedagogy and Elementary School Learning, 2025)
This study aims to describe the implementation of the Problem-Based Learning model in improving learning motivation, learning process, and learning outcomes of 20 fifth-grade students at SDN 08/II Rantau Duku. This type of research is Classroom Action Research (PTK) conducted in two cycles. The research instruments included questionnaires, teacher and student observation sheets, and learning outcome tests. Data analysis used a descriptive approach with qualitative and quantitative methods. The research success indicators were determined as follows: (1) at least 8% of students achieving a "good" level of learning motivation; (2) at least 75% of students actively participating in the learning process; and (3) measurable improvement in learning outcomes. These indicators referred to the Minimum Mastery Criteria (KKTP) of 70, which must be achieved by at least 80% of students. The results showed that: (1) learning motivation increased from 5 students (23,81%) who were highly motivated in the pre-cycle, to 11 students (52,38%) in cycle I, and 19 students (90,47%) in cycle II; (2) the learning process also improved, with 4 students (19,04%) actively participating in cycle I and 16 students (76%) in cycle II in the “good” category; (3) learning outcomes showed significant improvement, from 12 students (60%) achieving mastery in cycle I to 18 students (86%) in cycle II. It can be concluded that the implementation of the PBL model was effective in improving the motivation, engagement, and academic achievement of fifth-grade students at SDN 08/II Rantau Duku as a whole.